2014
DOI: 10.1088/1742-6596/480/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Fe50Co50 nanostructured alloy

Abstract: Enhanced magnetic studies of Fe50Co50 thin film on Si (1 1 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
4
1
Order By: Relevance
“…From Figure 7a, it could be observed that the crystallite size decreased from a value of 173.7 nm at 0 h down to a value of 13.6 nm at 30 h of milling for the Fe phase. These results differ from the values reported by Yepes et al (2014) who found a crystallite size of 7.5 nm at 35 h of milling. The difference between these values could result from the experimental conditions used for the mechanical alloying process of the powders.…”
Section: Characterization By Xrdcontrasting
confidence: 99%
See 2 more Smart Citations
“…From Figure 7a, it could be observed that the crystallite size decreased from a value of 173.7 nm at 0 h down to a value of 13.6 nm at 30 h of milling for the Fe phase. These results differ from the values reported by Yepes et al (2014) who found a crystallite size of 7.5 nm at 35 h of milling. The difference between these values could result from the experimental conditions used for the mechanical alloying process of the powders.…”
Section: Characterization By Xrdcontrasting
confidence: 99%
“…The decrease in size of aggregates particles as the milling time increases is characteristic of the milling process. All the observations for Fe 50 Co 50 agree with those obtained for the same composition milled for 8, 20 and 35 h (Yepes et al, 2014).…”
Section: Morphological Characterization By Semsupporting
confidence: 85%
See 1 more Smart Citation
“…It should be noted that the composition of the Fe50Co50 and Fe65Co35 nanostructured powders were formed after 8 hours of milling and the size of the crystallite reduction with the increase of the milling time. However, a lower value in the crystallite size was obtained after 7.5 nm to 35 hours of milling (Yepes et al, 2014). From the aforementioned investigations, it was possible to demonstrate that characterizations of the FeCo system have been made using scanning electron microscopy, x-ray diffraction, and vibrating sample magnetometry techniques.…”
Section: Introductionmentioning
confidence: 97%
“…This way, from the AM method, the structure and magnetic properties of the system are considered (Pérez et al,2012, Rincón et al, 2017. Similarly, the preparation of nanostructured powders of Fe50Co50 composition and their morphological characterization by SEM and DRX has been reported in (Yepes et al, 2014). It should be noted that the composition of the Fe50Co50 and Fe65Co35 nanostructured powders were formed after 8 hours of milling and the size of the crystallite reduction with the increase of the milling time.…”
Section: Introductionmentioning
confidence: 99%